Converging versus reconstituting environmental ethics - Rolston, Holmes, 1932-2025, author; Temple University Press, publisher (Colorado State University. Libraries, 2009)
Bryan Norton's "convergence" initially implies starting from differing points and reaching the same state, as with convergent evolution. The convergence of anthropocentrism and non-anthropocentrism comes by Norton's drawing back from any intrinsic value in nature. Yet his ever more enlightened anthropocentric goals come increasingly to coincide with what nonanthropocentrists also desire. This is reconstituting environmental ethics. He can win only by moving the goal posts.
Keywords: conservation; environmental ethics; convergence; millennium ecosystem assessment; ecosystems